The Little Engine That Could - Piper, Watty pseud; Hauman, George; Hauman, Doris (New York Grosset & Dunlap, 2009)
Although she is not very big, the Little Blue Engine agrees to try to pull a stranded train full of toys over the mountain.
Keywords: Railroad trains -- Juvenile fiction; Toys -- Juvenile fiction; Determination (Personality trait) -- Juvenile fiction; Helping behavior -- Juvenile fiction; Railroad trains -- Fiction; Toys -- Fiction; Determination (Personality trait) -- Fiction; Helpfulness -- Fiction